Study of metal coating on lead-free high refractive index glass prepared from local sand - Pisutti Dararutana (2018)
Lead-containing glasses coated with lead metal have been used for decoration in Thailand for a long time, were a high refractive index glass. Due to harmful effects of lead, time degradation of glass and because of many kinds of local raw materials for glass production especially sand, colorless lead-free high refractive index glasses were prepared by using local raw materials. In this work, the various kinds of metals; silver and aluminum, were coated on the surface of the prepared glasses using both chemical and physical methods. The joining interfacial layer between the glass body and the coated layer was studied using a scanning electron microscope and the hardness of the coated glasses was measured by a microhardness tester to compare with those of lead coating. It was found that the structures between the joining interfacial layers were similar. The values of the Knoop hardness were approximately 520±20 kg/mm2. This glass can be used to replace the lead glass for restoration glass or decoration onto the surface of the new wood or the metal carving products.